(untitled) (Journal of actual problems of jurisprudence, 2019)
Article provides information about features of the legislative process of recognition of private property in the Republic of Kazakhstan and its equality with the state property. Also the stages of property relations development in the Republic of Kazakhstan are considered and main characteristics and development directions of property relations are defined. Articlke also provide information about main factors influencing the property relations in the state. Keywords: The Constitution of the Republic of Kazakhstan, the Land Code of the Republic of Kazakhstan, the right to private ownership of land, the right of state ownership of land, the land, the land owner, the state.